Clinical and electromyographic signals analysis about the effect of space-adjustment splint on overerupted maxillary molars - Qun Lei; Dong Lin; Kaijin Lin; Wenxiu Huang; Dong Wu; Yuyu Liu (BMC, 2024)
Abstract Background Overerupted maxillary molars is common in adults, which can lead to insufficient intermaxillary vertical space ,great difficulty in prosthetic reconstruction ,and cause occlusal interference in movements.To reconstruct occlusal function, it is necessary to prepare enough space for prostheses. The aim of the present study was to evaluate the effect of space-adjustment occlusal splint on overerupted maxillary molars by clinical and electromyographic signals analysis. Methods Eighteen patients with overerupted maxillary molars were selected to wear space-adjustment occlusal splint suppressing overerupted maxillary molars for three months. Satisfaction was assessed by 5-point Likert; intermaxillary vertical space and the teeth transportation distance were measured in models; clinical periodontal status were evaluated by periodontal probing depth (PPT) and bleeding index (BI); electromyographic recordings of the masseter and anterior temporal muscles were monitored by Cranio-Mandibular K7 Evaluation System. Results All the patients were satisfied with the treatment effect (Likert scale ≧ 4). The intermaxillary space in edentulous areas after treatment showed statistically significant increasing when compared with those before treatment. PPT and BI showed no significant difference. No statistically significant differences were found in electromyographic activity of anterior temporal muscles, while a reduction of muscle activity in masseter in the contralateral side were detected in post-treatment evaluations compared with pre-treatment at mandibular rest position. Conclusions Space-adjustment occlusal splint is an efficient treatment option on overerupted maxillary molars by intruding the maxillary molar to obtain adequate intermaxillary space for prostheses.